Psikoedukasi “Remaja MUDA” untuk Meningkatkan Asertivitas Anti-Seks Pranikah - Yenny Sandria Alexander; Bhina Patria (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
This study aimed to increase the understanding of sexuality at the age of puberty through "Remaja MUDA" psychoeducation to increase anti-premarital assertiveness. The module validation was conducted in two phases. First, the content validity was conducted through judgement from ten raters. The results of Aiken’s V analysis showed score sbetween 0,8-0,975 which means that the module has good content validity. Second, the empirical tests to determine the effect of modules on anti-premarital sex assertiveness. This research was quasi-experimental research using an untreated control group design with pretest and posttest. The participants were 30 junior high school students (aged 13 to 14) in Yogyakarta. The results of independent samples t-test showed that anti-premarital sex assertiveness in the experimental group had a significant difference compared to control group (t = -10.063; p < 0.05). The results of the study indicated that the "Remaja MUDA" module can be used to increase anti-premarital sex assertiveness.